الدكتور محمد راتب النابلسي و جهوده في الإعجاز العلمي - عمير، أحمد خضير; خضير، إسماعيل مخلف Khudair, Ismail Mekhlef (ديوان الوقف السني - مركز البحوث والدراسات الاسلامية, 2014)
The search consists the saying about important character in the Islamic history where he talks about his invocation activity in showing the Qur’anic miracles as mentioned in the wise Qur’anic verses
Keywords: العلماء المسلمون -- النابلسي، محمد راتب -- القرآن الكريم -- تفسير القرآن -- الإعجاز العلمي